1998
DOI: 10.1097/00042560-199812010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Mexiletine for HIV-Infected Patients With Painful Peripheral Neuropathy: A Double-Blind, Placebo-Controlled, Crossover Treatment Trial

Abstract: Although mexiletine, an antiarrhythmic with local anesthetic properties, has been reported to relieve discomfort in diabetic neuropathy, its usefulness in the treatment of HIV-related painful peripheral neuropathy (PPN) has not been determined. The tolerance and effectiveness of mexiletine in HIV-related PPN were assessed in 22 patients who were randomized to receive mexiletine (maximum dose, 600 mg/day) or placebo for 6 weeks, followed by the alternative intervention for 6 weeks after a 1-week washout period.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 20 publications
0
30
0
2
Order By: Relevance
“…There is one randomized, controlled trial (199) that demonstrated an analgesic effect in peripheral nerve injury. With regard to other types of pain, studies to date have found no significant analgesic effect for mexiletine in HIV neuropathy (48,200), spinal cord injury (201) or prevention of the onset of chronic pain subsequent to breast surgery for cancer (202,203).…”
Section: Other Agents Used For Chronic Painmentioning
confidence: 99%
“…There is one randomized, controlled trial (199) that demonstrated an analgesic effect in peripheral nerve injury. With regard to other types of pain, studies to date have found no significant analgesic effect for mexiletine in HIV neuropathy (48,200), spinal cord injury (201) or prevention of the onset of chronic pain subsequent to breast surgery for cancer (202,203).…”
Section: Other Agents Used For Chronic Painmentioning
confidence: 99%
“…Cependant, malgré ce mode d'administration et une meilleure biodisponibilité, les effets de la méxilétine n'ont pas été très concluants. En effet, aucun effet bénéfique n'a été observé dans le traitement des neuropathies périphériques et des neuropathies associées au sida ou aux lésions de la moelle épinière [18,49,51]. Des effets analgésiques ont été observés dans le cas de neuropathies associées à des lésions de nerfs périphériques [16] ou des neuropathies diabétiques [26] mais à des concentrations excessives (supérieures à 600 mg/j).…”
Section: Sous-unités Bunclassified
“…Therapeutic trials reporting partial relief include the use of amitriptyline (Kieburtz et al, 1998), mexiletine (Kemper, Kent, Burton, & Deresinski, 1998;Kieburtz et al, 1998), peptide T (Simpson, Dorfman, Olney, et al, 1996), acupuncture (Shlay et al, 1998), topical capsaicin (Paice et al, 2000), and lamotrigine (Simpson et al, 2000).…”
Section: Treatment Modalities For Distal Symmetrical Peripheral Neuromentioning
confidence: 99%